Interpersonal knowledge transfer within the multinational enterprise: incorporating identity based quasi-formal knowledge governance mechanisms. Issue 2 (25th February 2022) - Sharma, Revti Raman; Phookan, Himadree
Abstract : Purpose: The paper aims to incorporate the social identity theory perspectives to the knowledge-based view in order to suggest how certain organizational characteristics can be leveraged as knowledge governance mechanisms for interpersonal knowledge transfer within the multinational enterprise (MNE). Design/methodology/approach: This paper is a conceptual discussion on interpersonal knowledge governance mechanisms. Findings: The paper proposes a new set of governance mechanisms which may be leveraged to govern interpersonal knowledge transfer. These mechanisms utilize organizational identity of individuals to govern individual level knowledge transfer behavior with the MNE. The paper also illustrates how subsidiary power, one of such mechanisms, influences interpersonal knowledge transfer within the MNE through organizational identification. Research limitations/implications: As the paper is conceptual, the proposed mechanisms have not been substantiated empirically. It calls for empirically testing the suggested mechanisms across countries. Practical implications: The paper provides insights to managers for leveraging on organizational identity to manage interpersonal level knowledge transfer within the MNE. Originality/value: The paper adds organizational identity-based knowledge governance mechanisms to the knowledge governance approach. It highlights how certain organizational characteristics (e.g. subsidiary power), even though these are not knowledge governance mechanisms per se, can be utilized to govern interpersonal knowledge transfer with the MNE.